1987
DOI: 10.2307/3282307
|View full text |Cite
|
Sign up to set email alerts
|

Key to the Families and Subfamilies of Acanthocephala, with the Erection of a New Class (Polyacanthocephala) and a New Order (Polyacanthorhynchida)

Abstract: A key to the classes, orders, families, and subfamilies of Acanthocephala based on the Meyer-Van Cleave system as presented by Amin (1985) is provided. A new class (Polyacanthocephala) and a new order (Polyacanthorhynchida) are erected to accommodate members of the monogeneric family Polyacanthorhynchidae Golvan, 1956.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 1 publication
3
82
0
3
Order By: Relevance
“…The phylum has been traditionally divided into three classes, Archiacanthocephala, Palaeacanthocephala, and Eoacanthocephala (Amin, 1985;Bullock, 1969), although a new class, Polyacanthocephala, with one order, one family, one genus (Polyacanthorhynchus), and four species has been recently proposed (Amin, 1987). Three of these species, P. macrorhynchus, P. caballeroi, and P. rhopalorhynchus, inhabit the digestive tract of south American calmans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylum has been traditionally divided into three classes, Archiacanthocephala, Palaeacanthocephala, and Eoacanthocephala (Amin, 1985;Bullock, 1969), although a new class, Polyacanthocephala, with one order, one family, one genus (Polyacanthorhynchus), and four species has been recently proposed (Amin, 1987). Three of these species, P. macrorhynchus, P. caballeroi, and P. rhopalorhynchus, inhabit the digestive tract of south American calmans.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, characters such as trunk spination, lacunar canal location, number and size of proboscis hooks, female ligament sacs, and male cement gland nuclei have been used to support the Polyacanthocephala as a new class (Amin, 1987). In this study we sequenced the nearly complete 18S ribosomal RNA gene of P. caballeroi and Rhadinorhynchus sp., which were aligned with 21 sequences of acanthocephalans representing the classes Archiacanthocephala, Palaeacanthocephala, and Eoacanthocephala.…”
Section: Introductionmentioning
confidence: 99%
“…T he new species, Acanthocephalus reunionensis, with a cylindrical proboscis with many hooks, double walled proboscis receptacle, six cement glands, parasitic in freshwater fishes, keys down to the family Echinorhynchidae and having a cylindrical trunk without spines, to the subfamily Echinorhynchinae (see Amin, 1987). Having only hooks, no spines, on the proboscis, hooks larger mid proboscis than anteriorly or posteriorly, lemnisci sacciform and testes in the posterior half of the trunk, the new species falls within the genus Acanthocephalus as defined by Golvan (1969).…”
Section: Discussionmentioning
confidence: 99%
“…Metacestodes were found encysted in large numbers along the viscera, and it was not possible to count them. Nematodes were identified and classified according to TRAVASSOS et al (1928) and MORAVEC (1998), respectively, and acanthocephalans were identified following NICKOL & THATCHER (1971) and classified according to AMIN (1987). Ecological terms, prevalence, mean intensity, mean abundance and site of infection follows BUSH et al (1997).…”
Section: Methodsmentioning
confidence: 99%